2021
DOI: 10.3390/nu13072375
|View full text |Cite
|
Sign up to set email alerts
|

The Diabetes Eating Problem Survey-Revised (DEPS-R) in a Greek Adult Population with Type 1 Diabetes Mellitus: Model Comparison Supporting a Single Factor Structure

Abstract: Type 1 diabetes mellitus (T1DM) patients occasionally develop disordered eating behaviors, leading to insulin manipulation without medical consultation, targeting to achieve weight control. In clinical practice, the Diabetes Eating Problem Survey-Revised Version (DEPS-R) questionnaire has been used to evaluate eating disorders in T1DM patients. This study was conducted to validate the factor structure of the Greek version of DEPS-R using Confirmatory Factor Analysis (CFA), to investigate its reliability and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
16
2
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(25 citation statements)
references
References 27 publications
5
16
2
2
Order By: Relevance
“…In the present study, 16.5% of the participants enrolled were positively screened for DEBs. This result is comparable with data collected by cross-sectional studies in children and adolescents with T1D from all over the world (17.4% for Egyptian [ 5 ], 25% for Turkish [ 6 ], 13.8% for Norwegian [ 7 ], 39.3% for Chinese [ 8 ], 30.1% for Greek [ 9 ], and 28.1% for Italian populations [ 4 ]). Results from this study are in line with what the available literature specifies around adolescence and T1D [ 31 ], meaning that this age is the most difficult in terms of psychosocial adjustment to the illness as well as correct adherence to therapy.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In the present study, 16.5% of the participants enrolled were positively screened for DEBs. This result is comparable with data collected by cross-sectional studies in children and adolescents with T1D from all over the world (17.4% for Egyptian [ 5 ], 25% for Turkish [ 6 ], 13.8% for Norwegian [ 7 ], 39.3% for Chinese [ 8 ], 30.1% for Greek [ 9 ], and 28.1% for Italian populations [ 4 ]). Results from this study are in line with what the available literature specifies around adolescence and T1D [ 31 ], meaning that this age is the most difficult in terms of psychosocial adjustment to the illness as well as correct adherence to therapy.…”
Section: Discussionsupporting
confidence: 85%
“…A recent Italian cross-sectional study of 690 adolescents with T1D estimated a DEB prevalence of 28.1% (21% boys, 35% girls) [ 4 ]. Similar results have been reported for other adolescent populations with T1D across the world [ 5 , 6 , 7 , 8 , 9 ]. A population-based study from national registers in Sweden and Demark investigated the within-individual association between T1D and eating disorders, highlighting a risk of 2% of developing a subsequent eating disorder in this population [ 10 ].…”
Section: Introductionsupporting
confidence: 89%
“…Another EFA study in Greek [ 33 ] adults revealed four factors (diet, weight loss, insulin use and compensatory behaviors) explaining 65.68% of the total variance, but it included a small sample of 100 participants. Recently, another Greek study on 100 adults using confirmatory factor analysis supported a single-factor model among T1D adult patients [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…DEPS-R has been translated and validated among T1D and T2D patients at different ages in different countries, such as Germany [ 17 ], Norway [ 18 ], Turkey [ 19 ], Spain [ 20 ], Italy [ 21 ], Canada [ 22 ], China [ 23 ] and Greece [ 24 ]. However, there is no validated Arabic version of the DEPS-R.…”
Section: Introductionmentioning
confidence: 99%
“…También un IMC más alto antes del diagnóstico, baja autoestima o antecedentes de depresión, insatisfacción corporal, diagnóstico de diabetes entre los 7 y 18 años de edad, y los antecedentes familiares de dieta o trastornos de la alimentación (Candler et al, 2018). Otros factores pueden ser los comentarios negativos de familiares, amigos y conocidos, y posiblemente la disminución de la vida sexual y las dudas sobre su aceptación por parte del sexo opuesto (Karastogiannidou et al, 2021).…”
Section: Introductionunclassified